Kolhāpūra Portugeja sambandha : Govā Purābhileka Saṅgrahālayāntūna nivaḍalele kāgada - Śiroḍakara, Pra. Pā (Yaśavantarāva Śã. Taste, 1979)
Collected Portuguese documents at the Goa Archives, Panaji, concerning the relations of the Portuguese in India with the Maratha states, Kolhapur, Sawantwadi, and Satara.